Pengaruh Pajak (Etr), Tunneling Incentive (Tnc), Mekanisme Bonus (Itrendlb) Dan Firm Size (Size) Terhadap Keputusan Transfer Pricing (Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Periode 2017-2020) - Fany Setyorini; Ida Nurhayati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
Transfer pricing is a policy on transfer prices, including: selling prices of goods or services, and intangible assets to subsidiaries or related parties located in their country or in other countries. Currently, many national companies have turned into multinational companies. The difference between national and multinational companies is in the location of the company's operations, this makes the company's operational activities not only concentrated in one country. The impact of this resulted in differences in regulations and policies, especially in taxes. For the government, taxes are a source of state treasury revenue, while for companies, taxes are a burden that must be paid to the state. Transfer pricing is carried out to obtain maximum profit. The purpose of this study is to examine the effect of Taxes, Tunneling Incentives, Bonus Mechanisms and Firm Size on Transfer Pricing decisions in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. The sample was obtained using purposive sampling method with several criteria, the results obtained a sample of 163 companies. Hypothesis testing was carried out using multiple linear regression with the help of SPSS 25. The results of this study indicate that the tax and bonus mechanism has no effect on transfer pricing at a significance level of 0.467 > 0.05 and 0.68 < 0.05. Tunneling incentive and firm size affect transfer pricing with a significance level of 0.014 < 0.05 and 0.043 < 0.05. The value of Adjusted R Square is 5.9% while the remaining 94.1% is influenced by other variables not examined in this study.